Development of official statistics models for analysis of population sectoral data in Indragiri Hilir Regency - Alfassa, Achmad Isya (EDP Sciences, 2023)
Indragiri Hilir Regency is one of the regencies located in Riau Province which has a population of 658,025 thousand in 2022. The population consists of several groups ranging from children, adolescents, adults and the elderly. Indragiri Hilir Regency has three regional public hospitals, namely the Puri Husada Tembilahan Hospital, the Tenku Sulung Pulau Kijang Hospital, and the Raja Musa Sungai Guntung Hospital. Each hospital has official statistics consisting of sectoral data according to the data owned by the hospital. This study aims to show and analyze the existing official statistics and create an official statistics model for analysis of population sectoral data in health analysis. The method used is explanatory method and descriptive statistical analysis method and descriptive statistical analysis. The results of this study show that every regional public hospital in Indragiri Hilir Regency has official statistics which consist of sectoral data owned by the agency, the official statistics model is the answer to become a reference in carrying out sectoral data analysis for policy making in the field of analysis health. © 2023 EDP Sciences. All rights reserved.